Penyakit-Penyakit yang Dapat Merusak Tauhid dalam Islam - Hasanah, Mutiara; Sultani, Dalmi Iskandar (Melati Institute, 2025)
Diseases that can damage tawhid in Islam. Using qualitative research methods by applying literature studies, with data sources from literature both from books and journal articles related to the meaning of tawhid and diseases of tawhid in Islam. Shows that tawhid is a firm belief that there is no God but Allah and is the basis of aqidah, which means something that is believed by the heart. Tawhid prioritizes the oneness of Allah as explained in Surah Al-Ikhlas. Tawheed can be disturbed and even damaged by various diseases such as shirk, kufr, nifak, riya, bid'ah, apostasy, superstition, and khurafat, all of which damage the belief and purity of faith. Maintaining and maintaining true and straight beliefs is an obligation for every believing human being to stay on the path that is pleasing to Allah SWT, avoiding all threats that can damage faith.